Computational Methods in Financial Engineering Essays in Honour of Manfred Gilli - Kontoghiorghes, Erricos; Rustem, Berc; Winker, Peter (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Computational models and methods are central to the analysis of economic and financial decisions. Simulation and optimisation are widely used as tools of analysis, modelling and testing. The focus of this book is the development of computational methods and analytical models in financial engineering that rely on computation. The book contains eighteen chapters written by leading researchers in the area on portfolio optimization and option pricing; estimation and classification; banking; risk and macroeconomic modelling. It explores and brings together current research tools and will be of interest to researchers, analysts and practitioners in policy and investment decisions in economics and finance. "This book collects frontier work by researchers in computational economics in a tribute to Manfred Gilli, a leading member of this community. Contributions cover many of the topics researched by Gilli during his career: portfolio optimization and option pricing, estimation and classification, as well as banking, risk and macroeconomic modeling. The editors have put together a remarkable panorama of the rapidly growing and diversifying field of computational economics and finance." Michel Juillard, Paris School of Economics and University Paris 8.